Cover Image, Volume 94, Number 9, September 2022. Issue 9 (13th July 2022) - Yu, Ting; Ling, Qiao; Xu, Mengxin; Wang, Niu; Wang, Lixia; Lin, Hanwen; Cao, Manqi; Ma, Yong; Wang, Yuanyuan; Li, Kuibiao; Du, Liubing; Jin, Yunyun; et al.
Abstract : Front Cover Caption : The cover image is based on the Research Article ORF8 protein of SARS‐CoV‐2 reduces male fertility in mice by Ting Yu et al., https://doi.org/10.1002/jmv.27855 .